2014
DOI: 10.1074/jbc.m114.589564
|View full text |Cite
|
Sign up to set email alerts
|

First Demonstration of Transmissible Spongiform Encephalopathy-associated Prion Protein (PrPTSE) in Extracellular Vesicles from Plasma of Mice Infected with Mouse-adapted Variant Creutzfeldt-Jakob Disease by in Vitro Amplification

Abstract: Background: Prions can be transmitted by blood transfusion, but their origin and distribution in blood are unknown. Results: Prions were detected in plasma extracellular vesicles from preclinical and clinically sick mice. Conclusion: Prions associate with blood-circulating extracellular vesicles. Significance: These findings provide information about prion distribution in blood and set the groundwork for novel prion removal and disease diagnosis technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 93 publications
2
42
0
Order By: Relevance
“…This result confirms previous data showing the presence of PrP TSE in blood exosomes by the protein misfolding cyclic amplification (PMCA) method (Saá et al, 2014), in plasma by PMCA (Castilla et al, 2005) and real-time quaking-induced conversion assays (Orrú et al, 2011), and in human variant Creutzfeldt-Jakob disease patients by a solid-state binding matrix assay (Edgeworth et al, 2011), but adds the important novel information that PrP TSE , similarly to infectivity (Brown et al, 2001), is detectable in blood without using amplification techniques. The detection of PrP TSE by a standard Western blotting technique was only possible after reducing the interference of IgRES by exosomal pellet fractionation on a sucrose gradient.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…This result confirms previous data showing the presence of PrP TSE in blood exosomes by the protein misfolding cyclic amplification (PMCA) method (Saá et al, 2014), in plasma by PMCA (Castilla et al, 2005) and real-time quaking-induced conversion assays (Orrú et al, 2011), and in human variant Creutzfeldt-Jakob disease patients by a solid-state binding matrix assay (Edgeworth et al, 2011), but adds the important novel information that PrP TSE , similarly to infectivity (Brown et al, 2001), is detectable in blood without using amplification techniques. The detection of PrP TSE by a standard Western blotting technique was only possible after reducing the interference of IgRES by exosomal pellet fractionation on a sucrose gradient.…”
supporting
confidence: 79%
“…Because blood components probably interfere with PrP TSE detection (Hartwell et al, 2005;Abdel-Haq, 2015), we aimed to bypass this difficulty by looking at plasma exosomes. Exosomes are nanovesicles that carry RNA, proteins, lipids, other metabolites (Théry et al, 2009;Fais et al, 2013), PrP C and, in prion-infected hosts, PrP TSE and infectivity (Fevrier et al, 2004;Alais et al, 2008;Coleman et al, 2012;Saá et al, 2014).…”
mentioning
confidence: 99%
“…These results brought some hope to the possibility of detecting prions for the screening of blood for transfusion or other blood-derived products and importantly, for early diagnosis of prion diseases using an easily accessible body fluid. In fact, apart from the development of new PrP Sc detection methods for diagnosis, PMCA has permitted to detect PrP Sc in extracellular vesicles from plasma of vCJD infected mice [244], which was later confirmed by IHC [245]. Although other methods have been proposed (e.g., rapid tests based on ELISA [18,246], cellular assays using prion susceptible cells [247], or bioassay in Drosophila [248]), the worse specificity and sensitivity and difficulties associated to cell culture or fly models for standardization purposes have limited their use.…”
Section: Prp Sc In Blood According To New Detection Techniquesmentioning
confidence: 99%
“…121 Consistent with these in vitro findings, it has also been shown that EVs derived from plasma of mice infected with variant Creutzfeldt–Jakob disease (vCJD), one of the prion diseases, contains PRNP. 122 Due to the fact that transmission of vCJD has also been clinically reported to be associated with blood transfusion, 123 it is plausible to hypothesize that EVs might have a significant role in the transmission of prion diseases. Interestingly, upregulated miRNAs including let-7b, miR-146a, miR-103, miR-125a-5p and miR-342-3p were found to be present in the EVs isolated from human tissue samples affected with prion diseases, 124 suggesting thereby that PRNP-infected EVs also mediate the pathogenesis of prion disease through their contents in addition to spreading of PRNP.…”
Section: Prion Disease and Evsmentioning
confidence: 99%